Hitler's American countermodel: the United States and the making of Nazi ideology - Brunssen, Pavel (German politics and society, 2023)
Abstract The fact that the Nazis looked to the United States for inspiration has led some to claim that the US served Nazi thinkers as a “model.” This article argues instead that Nazis looked to America as a countermodel for how not to deal with the “Jewish question.” Through an intertextual analysis of visual and textual primary sources, this article demonstrates how the Nazis used America as a projection screen for developing their vision of empire and “redemptive antisemitism.” The Nazis admired the United States’ racist laws and technological development but despised Americans for ignoring the “Jewish threat.” By showing how the Nazis used the United States as a mirror for developing Nazi ideology, this article reintroduces the category of antisemitic ideology to the Historikerstreit 2.0 debate.